2014
DOI: 10.1073/pnas.1411270111
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic expression of the human FOXP2 speech gene

Abstract: The recent descriptions of widespread random monoallelic expression (RMAE) of genes distributed throughout the autosomal genome indicate that there are more genes subject to RMAE on autosomes than the number of genes on the X chromosome where X-inactivation dictates RMAE of X-linked genes. Several of the autosomal genes that undergo RMAE have independently been implicated in human Mendelian disorders. Thus, parsing the relationship between allele-specific expression of these genes and disease is of interest. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
(71 reference statements)
0
30
0
Order By: Relevance
“…In support of this view, all documented patients were heterozygous for the etiological mutation (Vernes and Fisher, 2009) in either the gene itself (point mutations, deletions, chromosomal rearrangements; e.g., Turner et al, 2013 and references therein) or downstream regulatory elements (e.g., Adegbola et al, 2015). Random mono-allelic expression (RMAE) with some cells having half the FOXP2 dosage and others expressing none at all (Adegbola et al, 2015) and mosaic deletion with some cells possessing two functional alleles and others none (Palka et al, 2012) also play a role.…”
Section: Introductionmentioning
confidence: 85%
“…In support of this view, all documented patients were heterozygous for the etiological mutation (Vernes and Fisher, 2009) in either the gene itself (point mutations, deletions, chromosomal rearrangements; e.g., Turner et al, 2013 and references therein) or downstream regulatory elements (e.g., Adegbola et al, 2015). Random mono-allelic expression (RMAE) with some cells having half the FOXP2 dosage and others expressing none at all (Adegbola et al, 2015) and mosaic deletion with some cells possessing two functional alleles and others none (Palka et al, 2012) also play a role.…”
Section: Introductionmentioning
confidence: 85%
“…In a study of SPCH1 families, O'Brien et al found that significant associations between the language phenotype and the markers around by not within FOXP2 ; one marker (D7S3052) is <5 Mb proximal and the other ( CFTR GATT repeat) is 3 Mb distal to FOXP2 [O'Brien et al, ]. It was shown recently that a 2 Mb deletion 3 Mb upstream of the FOXP2 gene impacts its expression in cis [Adegbola et al, ]. Similarly, a cis element >200 Kb downstream of FOXP2 was shown to have epigenetic characteristics of an enhancer; its displacement from the FOXP2 coding sequence resulted from a chromosomal inversion was postulated to be responsible for language impairment in a recent case [Becker et al, ; Moralli et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the low MAF for this variant in Han Chinese (<1%, compared to 24% in European cohorts) means this association is driven by a tiny number of individuals. A very large schizophrenia GWAS found no associations within FOXP2, but two signals mapped to a putative FOXP2 regulatory region that is deleted in CAS (1,140). Thus, whereas most FOXP2 association studies have targeted SNPs within the primary transcript or proximal promoter, future work should also consider variants in distal regulatory regions.…”
Section: Making the Most Of High-throughput Technologiesmentioning
confidence: 99%